Intermetallic compounds (IMC) formation during soldering [electronic resource] - Zureena Abu Samah, 1985- (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2008